Evaluating the readiness of selected hospitals of Tehran University of Medical Sciences to implement a clinical audit program from the viewpoint of hospital managers in 2018 - Hossein Darghahi; Kamran Irandoust; Seyyed Morteza Mojtabayan (Tehran University of Medical Sciences, 2019)
Background: The present research aimed to assess the readiness of selected hospitals of Tehran University of Medical Sciences to implement quality improvement programs and clinical audits from the viewpoint of managers. Materials and Methods: A descriptive-analytic study was conducted in May 2017 in four selected hospitals of Tehran University of Medical Sciences. The study population of this study was 20 managers of selected hospitals who were selected by census sampling method and entered the study. The data gathering tool was a two-part questionnaire whose validity and reliability were confirmed. In this study, we used SPSS software version 23 and statistical tests to analyze the data. Results: The effectiveness and readiness of hospitals to implement a clinical audit program was equal to 60% in the field of data and information, cardiology and feedback; 55% in resources, design and implementation, clinical audit management, and evidence and standards; 50% in illness and education; and 45% in manpower. Also, with increasing frequency of clinical audits, hospital readiness for quality improvement processes increases. Conclusion: Due to the effectiveness and low readiness of hospitals in implementing a clinical audit program, especially in the field of human resources (45%), it is necessary that managers and planners of clinical audit programs in hospitals have a precise knowledge of these factors in order to control the organizational environment and help improve the effectiveness of audit programs.